Relevance of main factors affecting radon concentration in multi-storey buildings in Liguria (Northern Italy) - Gallelli, G.; Panatto, D.; Lai, P.; Orlando, P.; Risso, D. (Journal of environmental radioactivity, 1998)
In 1991–1993 a series of 930 determinations of 222Rn concentration were performed in three rooms (kitchen, bedroom, living room) of private dwellings in Genoa and Savona, two neighbouring towns of Northern Italy. Our aim was to study the major factors influencing 222Rn concentration in multi-storey residential buildings. The main characteristic of each flat and the relevant weather conditions were recorded with a questionnaire. The results indicate that 222Rn contamination of the living environment was significantly higher in Savona, i.e. 33·8 (95% CI (16·1–71·0) Bq m -3 (geometric mean) than in Genoa, i.e. 16·8 (95% CI (9·9–28·6) Bq m -3 (geometric mean) where the radon precursors, i.e. uranium and radium, in the soil are significantly lower (2 ppm vs. 10 ppm). The major factors affecting indoor radon activity, besides local soil precursors concentration, were (a) storey level of the flat, (b) type of heating and (c) age of the building. Factor (b) probably depended on frequency of ventilation and factor (c) on differences in building materials. We could not evidence any influence due to the type of window frames and panes. The resulting effective dose equivalents calculated from the geometric means, were 0·5 and 1·0 mSv y -1 for the inhabitants of Genoa and Savona, respectively. The higher risk was attained by the subjects living on the ground level of old buildings with independent heating. In Italy the current trend is to modify the heating system of apartment buildings by increasing the number of independent flat furnaces. These changes may increase the risk of indoor radon exposure.